PEMBELAJARAN GEODIVERSITAS BERBASIS LAPANGAN BAGI GENERASI MUDA: STUDI EVALUATIF DI IJEN UNESCO GLOBAL GEOPARK - Muhammad Asyroful Mujib; Tri Rafika Diyah Indartin; Firda Diartika; Hablana Rizka; Kurnia Maulidi Noviantoro (Dinamika Sosial: Jurnal Pendidikan Ilmu Pengetahuan Sosial, 2026)
Ijen UNESCO Global Geopark has volcanic landscapes, distinctive geological formations, cultural heritage, and interconnected geosites that provide strong potential for geoscience education. However, this potential has not been fully accompanied by young people’s ability to understand Ijen as a geoheritage system that requires scientific interpretation and conservation. This study aims to evaluate field-based geodiversity learning for young people in Ijen UNESCO Global Geopark. An evaluative case study design was applied using descriptive quantitative and qualitative approaches. The research involved 50 participants, consisting of senior high school students, undergraduate students, master’s students, and young teachers. The learning activities were conducted over three days and two nights through field observation and interpretation at four main geosites: Kawah Wurung, Kalipait, Plalangan Black Lava, and Kawah Ijen. Data were collected through post-tests, geosite observation sheets, participant reflection notes, and field documentation. The results show that the average participant understanding score reached 79 out of 100. The highest score was obtained for understanding regional geosite values, at 82, followed by geoconservation and sustainable tourism, at 80, geopark functions, at 79, and geoheritage, at 75. These findings indicate that field-based learning effectively strengthens participants’ understanding of concrete and observable geosite aspects. However, geoheritage understanding still requires further reinforcement because it involves more abstract scientific, historical, educational, and conservation values. Field-based geodiversity learning is therefore relevant as a geopark education model for strengthening geoscience literacy, geoconservation awareness, and sustainable geotourism understanding among young people. ABSTRAK Ijen UNESCO Global Geopark memiliki lanskap vulkanik, formasi geologi khas, warisan budaya, dan jejaring geosite yang berpotensi sebagai ruang pendidikan geosains. Namun, potensi tersebut belum sepenuhnya diikuti oleh kemampuan generasi muda dalam memahami Ijen sebagai sistem geoheritage yang memerlukan interpretasi ilmiah dan konservasi. Penelitian ini bertujuan mengevaluasi pembelajaran geodiversitas berbasis lapangan bagi generasi muda di Ijen UNESCO Global Geopark. Penelitian menggunakan desain studi kasus evaluatif dengan pendekatan deskriptif kuantitatif dan kualitatif. Subjek penelitian berjumlah 50 peserta, terdiri atas siswa SMA, mahasiswa S1, mahasiswa S2, dan guru muda. Pembelajaran dilaksanakan selama tiga hari dua malam melalui observasi dan interpretasi lapangan pada empat geosite utama, yaitu Kawah Wurung, Kalipait, Plalangan Black Lava, dan Kawah Ijen. Data dikumpulkan melalui post-test, lembar observasi, catatan refleksi, dan dokumentasi lapangan. Hasil penelitian menunjukkan rata-rata skor pemahaman peserta mencapai 79 dari 100. Skor tertinggi terdapat pada pemahaman nilai geosite kawasan sebesar 82, diikuti geokonservasi dan pariwisata berkelanjutan sebesar 80, fungsi geopark sebesar 79, dan geoheritage sebesar 75. Temuan ini menunjukkan bahwa pembelajaran berbasis lapangan efektif memperkuat pemahaman peserta terhadap aspek geosite yang konkret dan mudah diamati. Namun, pemahaman geoheritage masih memerlukan penguatan karena berkaitan dengan nilai ilmiah, historis, edukatif, dan konservasi yang lebih abstrak. Pembelajaran geodiversitas berbasis lapangan relevan sebagai model edukasi geopark untuk membangun literasi kebumian, kesadaran geokonservasi, dan pemahaman geowisata berkelanjutan pada generasi muda.